THE INTERPLAY OF LANGUAGE AND POWER IN DISCOURSE ANALYSIS - Kalbayev Abdulaziz Shavkatovich; Abduramanova Diana Valerevna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: This article explores the intricate relationship between language and power through the lens of discourse analysis, a critical approach in sociolinguistics that examines how language shapes and is shaped by social hierarchies. Language is not a neutral tool but an instrument through which power is exercised, reinforced, and challenged in various social contexts, including politics, media, gender, and race. Discourse constructs reality, reflects societal norms, and perpetuates ideologies that maintain dominant power structures. Drawing on key theories from scholars like Foucault and Gramsci, the essay highlights how language serves to legitimize authority, control knowledge, and enforce social control, while also offering a means of resistance for marginalized groups.